母語優先的臺灣本土語言復振教育規劃 Mother Tongues First: Planning Taiwanese Native Languages Education Policy for Language Revitalization - 張學謙 Hak-Khiam Tiun (National Taiwan Normal University, 2020)
華語挾其政治、經濟、傳播、教育等勢力，入侵本土語言的家庭領域，進而取代傳統本土語言在家庭和社區的地位與功能。本土語言教育實施多年，族群母語卻仍然有流失、轉向使用華語的現象。本土語言持續流失，有必要重新構想臺灣本土語言教育規劃，以邁向本土語言復振。過去的本土語言教育場域集中在學校，缺乏和家庭和社區結合，也欠缺語言復振的理論指導。本文主張本土語言復振需要建構母語優先的雙語政策，透過整合式的語言復振教育模式，規劃家庭、社區和學校的母語防護圈；運用語言活力模式，在意識啟發、學校教育、校外擴展及世代傳承四個復振階段中，進行發展能力、創造機會以及提升意願的工作。本土語言的世代相傳為語言復振的核心，學校為主之語言復振常忽略了家庭語言傳承的面向，因此，本文特別強調家長能夠自我培力的家庭語言政策模式，從語言的意識、管理及實踐等面向，規劃本土語言返家，達成母語的世代傳承。以母語優先、跨語言實踐為方法，將本土語言融入課程當中，使之成為教學語言，開創更為豐富多元的本土語言空間。 The family domain as a base of native language has been invaded by Mandarin Chinese and its force in politics, the economy, communication and media, and education. Mandarin has replaced the traditional functions and positions of mother tongues in families and communities. Although mother tongue education has been implemented for years, a shift is occurring from mother tongues to Mandarin. Native language educational planning for language revitalization must therefore be reconsidered. In the past, mother tongue education was provided only in school and lacked support from families and communities and guidance from language revitalization theory. This article proposes that native language revitalization requires the inclusion of bilingual education that prioritizes mother tongues. A comprehensive language revitalization model is employed to establish a guarded section for mother tongues among families, communities, and schools. Applying a language vitality model into planning, developing language abilities, creating language opportunities, and increasing desires for language use can be practiced during each of the four steps of language revitalization-ideological awakening, school education, extension beyond school, and intergenerational language transmission. Bringing mother tongues home is the key to passing down languages throughout generations. It requires the application of family language policy and exploration of language ideology, management, and practice. The method of translanguaging can be adopted in school education so that the use of mother tongues as teaching languages can create additional spaces for mother tongue education.